Monitoring Land Use Change for Gentrification in Soho (London), Using Geographic Information Systems and Google Street View - Velastegui, Julia Desiree; Velastegui, Luis Alejandro; Moyon, Manuel Fabián (European Scientific Journal, ESJ, 2019)
Gentrification involves the substantial replacement of a neighborhood’s lower-income residents with newcomers of higher income who renovate and upgrade the neighborhood. Although gentrification is first and foremost a residential process, it also entails commercial redevelopment. As the socioeconomic composition of the neighborhood changes, so it does the perception of acceptable land uses. In Soho, displacement has affect residents and local business in the same way, but the attention has been focused in the cultural and entertainment activities that have been currently disappearing, since once they were the heart of this neighborhood. The principal aim of this study is to develop a methodology to keep geographic land-use databases updated in order to analyze the spatial variability related with gentrification process of Soho. This study shows a methodology to keep geographic land-use database updated using Geographic Information Systems, through the use of panoramic photos captured by Google Street View. Since the panoramic photos from different years are now available, Google Street View could become a new tool to perceive, observe and study neighborhood changes in Soho during the years 2008, 2012, 2014 and 2015. Based on the obtained maps, there is a representative spatial variability that land uses show in Soho, as regardless the reduced extension of this area, the centroids are constantly moving from year to year. Therefore, Geographic Information Systems and Google Street View are useful tools to keep updated geodatabases; however, for future work it is recommended the inclusion of Volunteered Geographic Information.